ANALYSIS OF LONG TERM RESULTS OF MYOCARDIAL REVASCULARIZATION IN PATIENTS WITH STABLE ISCHEMIC HEART DISEASE WITH A HIGH LEVEL OF TREATMENT ADHERENCE - N. Yu. Sokolova; E. Z. Golukhova; K. V. Shumkov; E. V. Kuznetsova (Кардиоваскулярная терапия и профилактика, 2017)
Aim. To compare long term results of different methods of myocardial revascularization in patients with stable ischemic heart disease.Material and methods. In the study, 352 patients included, with stable ischemic heart disease: mean age 57,6±7,7 y.o. underwent coronary bypass operation (CBG) — group 1 (n=183) and percutaneous coronary interventions (PCI) — group 2 (n=169) with drug eluting stents implantation (1st generation — Taxus, Cypher), with high treatment adherence — medication treatment in postsurgery period. Each group was selected to 2 subgroups: 1 subgroup with 1-2 vessel disease, 2 subgroup with main left coronary artery stem disease and/or severe multivessel disease. Primary endpoints: all-cause mortality, cardiac mortality, non-fatal myocardial infarction, non-fatal stroke. Secondary endpoint: repeated revascularization or appearance of indications to it. Mean time of follow up after CBG was 37,9±6 months.Results. In long term period there were no differences in survival between groups CBG and PCI neither in 1-2-vessel lesion (95,5% vs. 96,8%), nor with stem stenosis or multivessel disease — 95,6% vs 94,1%. Also, there were differences in survival rate depending on the grade of patient comorbidity, regardless revascularization method. There were no differences in groups 1 and 2 in cardiac mortality, nonfatal events. Emerging of indications for repeated myocardial revasculariztion was significantly higher in subgroups with multivessel disease: free from revascularizations, respectively, 97,1% vs 88,0%, in CBG and PCI (p=0,34).Conclusion. Long term survival after PCI with drug eluting stents of 1st generation in comparison to CBG, does not show significant differences in patients with different severity of coronary arteries lesion and high adherence to treatment. However there is dependence on comorbidity evel. Repeated revascularization of myocardium is needed more oftenly after endovascular interventions in stem lesion and/or multivessel disease.